Frequent but fragmented: use of note templates to document outpatient visits at an academic health center. (19th October 2021) - Rule, Adam; Hribar, Michelle R
Abstract: Recent changes to billing policy have reduced documentation requirements for outpatient notes, providing an opportunity to rethink documentation workflows. While many providers use templates to write notes—whether to insert short phrases or draft entire notes—we know surprisingly little about how these templates are used in practice. In this retrospective cross-sectional study, we observed the templates that primary providers and other members of the care team used to write the provider progress note for 2.5 million outpatient visits across 52 specialties at an academic health center between 2018 and 2020. Templates were used to document 89% of visits, with a median of 2 used per visit. Only 17% of the 100 230 unique templates were ever used by more than one person and most providers had their own full-note templates. These findings suggest template use is frequent but fragmented, complicating template revision and maintenance. Reframing template use as a form of computer programming suggests ways to maintain the benefits of personalization while leveraging standardization to reduce documentation burden.